Policing Firearm Regulation and Crime Control: Criminological Insights from the Philippine National Police in Amadeo, Cavite - Rile F. Vill ariez Jr.; Elizabeth Buena-Villa; Julius Guiller G. Luis (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
The study findings indicate that while information campaigns are active, physical enforcement is hindered by logistical gaps and inconsistent community reporting. Possession of illegal firearm and trafficking persist despite RA10591 regulations, causing increased gun-related crimes and fatalities, with 7,702 deaths in the Philippines in 2014. Inadequate monitoring and enforcement of RA10591's provisions create loopholes that allow individuals to circumvent the law, posing a threat to public safety. The study was performed out at Cavite's Amadeo. The Amadeo Police Station's officers were the responders. Purposive sampling was used in their selection. It used qualitative research, and interviews were used to get relevant data. The findings revealed that majority of the survey participants were police officers with the rank of Police Master Sergeant though other ranks were represented. Majority were college graduates who served for many years reflecting expertise and dedication maintaining weapon safety and control. The PNP takes initiatives increasing public understanding of the Comprehensive Firearms and Ammunition control Act. However, face a number of difficulties, such as a lack of funding and public opposition to some programs.